Alcohol dehydrogenase in Drosophila: isolation and characterization of messenger RNA and cDNA clone. - Benyajati, C (1980)
The mRNA for alcohol dehydrogenase (ADH) in D. melanogaster has been identified by translation in a cell-free system. The in vitro synthesized polypeptide, specifically precipitated by anti-ADH antibody, has identical subunit molecular weight (25,000 daltons) and tryptic peptide profile to the in vivo synthesized ADH. The poly A containing ADH-mRNA has been purified by specific precipitation of ADH-polysomes using anti-ADH antibody and S. aureus. Transformation of E. coli with the dA-tailed ADH-mRNA-complementary DNA hybrid annealed to the dT-tailed pBR322 yielded one plasmid which has been identified as the ADH-cDNA clone. The identification involved hybridization selection of ADH-mRNA and in vitro translation, in situ hybridization to the Adh locus on salivary gland polytene chromosomes and DNA sequencing. This ADH-cDNA plasmid contains 349 bases of the C-terminal protein coding and 180 bases of the 3' untranslated region.